In-service Development For Graduate Teaching Assistants: A Blended-learning And Formative Approach - Santandreu Calonge, David; Chiu, Patrio; Thadani, Dimple; Mark, Kai Pan; Pun, Cecilia F.K (Journal of University Teaching and Learning Practice, 2011)
Graduate Teaching Assistants (GTAs) are front-line facilitators with first-hand contact with students. They play an important role in providing an engaging learning experience for undergraduate and postgraduate students. However, most of them have not received adequate training and guidance in teaching. This paper reports on an intensive and compulsory education development course for postgraduate students, which aims to prepare them for their upcoming teaching role whilst they are still research students; The course provides an introduction to the basic theoretical knowledge and practical skills required before they begin to take up teaching responsibilities at the University, in a Chinese (Hong Kong/Mainland China) and English Medium Instruction context. Blended learning technologies, active learning strategies, formative assessment and an outcomes-based approach are extensively used throughout the course to enable and encourage participation and collaboration. To measure the outcome performance of the course in alignment with the University’s strategic goals, a number of key performance indicators are assessed. The result shows that students found the course very useful and the blended instructional methods used facilitated the achievement of the Intended Learning Outcomes.